The role of vertical disparities in the oblique effect - Aznar-Casanova,J. Antonio (2008)
A great deal of studies using different visual tasks (e.g., Vernier acuity tasks, tilt illusion, crowding, etc) have revealed that our perception is strongly influenced by the orientation of the stimulus. Most studies have investigated visual acuity in two-dimensional visual spaces (2D) but little is known about the effect of line orientation in depth perception (3D). In one experiment, Vernier Acuity (VA) in frontoparallel (2D) and medial (3D) planes was investigated. We used a virtual reality setup inducing inter-ocular disparities to simulate a 3D visual space, and a common computer screen to present stimuli in the frontal plane. In the experiment, by using the method of constant stimuli, the observer compared VA in the 2D and 3D visual spaces as a function of the stimulus orientation. Results showed that only judgments in the 3D condition were affected by the well-known 'oblique effect', and some impairment in stereoacuity (lines in depth plane) in comparison to 2D acuity (lines in frontal plane) was observed. We attributed the cause for such deterioration in stereoacuity to changes in vertical disparities.